An Enantiopure Propeller‐Like Trityl‐Brominated Radical: Bringing Together a High Racemization Barrier and an Efficient Circularly Polarized Luminescent Magnetic Emitter. Issue 17 (13th March 2020) - Mayorga‐Burrezo, Paula; Jiménez, Vicente G.; Blasi, Davide; Parella, Teodor; Ratera, Imma; Campaña, Araceli G.; Veciana, Jaume
Abstract: A new persistent organic free radical has been synthetized with Br atoms occupying the ortho ‐ and para ‐positions of a trityl core. After the isolation of its two propeller‐like atropisomers, Plus ( P) and minus ( M ), their absolute configurations were assigned by a combination of theoretical and experimental data. Remarkably, no hints of racemization were observed up to 60 °C for more than two hours, due to the higher steric hindrance imposed by the bulky Br atoms. Therefore, when compared to its chlorinated homologue ( t 1/2 =18 s at 60 °C), an outstanding stability against racemization was achieved. A circularly polarized luminescence (CPL) response of both enantiomers was detected. This free radical shows a satisfactory luminescent dissymmetry factor (|glum (592 nm)|≈0.7×10 −3 ) despite its pure organic nature and low luminescence quantum yield (LQY). Improved organic magnetic CPL emitters derived from the reported structure can be envisaged thanks to the wide possibilities that Br atoms at para ‐positions offer for further functionalization. Abstract : Get radical ! An efficient circularly polarized luminescence emitter, based on a persistent trityl radical substituted with bulky bromine atoms at ortho ‐ and para ‐positions, is reported (see figure). In addition, this emitter has a high racemization barrier between its enantiomers.